Establishment of seamless care study society and introduction of the critical path for healthcare network management - Tatara, Kiyomi; Ohara, Masaki; Fujimoto, Shunichiro (The Journal of Japan Society for Health Care Management, 2006)
The Seamless Care Study Society was established in the central and western part of Kagawa Prefecture in November. 2005, for the purpose of a continuous community-health-care cooperation without interruptions between acute stage hospital stays and patients' home. Up to July 2006 seven study workshops with36institutions and 196 persons' participating were held. Participants' occupations were various including physicians, nurses, physical therapists, occupational therapists, speech therapists, dietitians, care managers and administration officials. The range of cooperation includes care from an acute stage hospital to being home as well as standardization of medical treatment and rehabilitation steps and the use of a common language in every institute. Liaison critical paths of “cerebral apoplexy”, of “femoral neck fracture”, and of “swallowing difficulty and NST” were drawn up by three study groups, and are already implemented. Results will be analyzed by a case conference and a variance check and further improvement of a critical path will be implemented in the future.